ECONOMIC ASSESSMENT OF AGRICULTURAL ENTERPRISES IN IVANO-FRANKIVSK REGION, UKRAINE - IDENTIFICATION OF FACTORS THAT INFLUENCE PERFORMANCE - Tetiana KUZMIN; Ivan BALANIUK; Diana SHELENKO; Oleksandr SHPYKYLIAK; Myshailo SMUSHAK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
As part of the study, the methodological toolkit for the functioning of land relations is substantiated. Using the software product STELLA, a system analysis was conducted to forecast trends in the development of indicators of agricultural enterprises. The gross output of agricultural enterprises was selected as an effective indicator, and the size of land plots was one of the influencing factors. It has been proven that forecasting is an important direction in the development of land relations in agricultural enterprises in modern competitive conditions. On the basis of the system analysis, modeling was carried out using the STELLA software product. The forecast of the production of gross agricultural products by enterprises of the Ivano-Frankivsk region until 2030 was carried out. The study shows, that among the main factors affecting the dynamic of the production of the gross products by agricultural enterprises according to its volume, the amount of mineral fertilizers applied per 1 hectare of land, the number of employees in enterprises and the number of animals in conditional expression are singled out.